Monitoring ground deformation of cultural heritage sites using UAVs and geodetic techniques: the case study of Choirokoitia, JPI PROTHEGO project - Themistocleous, Kyriacos; Danezis, Chris; Mendonidis, Evangelos; Lymperopoulou, Efstathia (My University, 2017)
This paper presents the integrated methods using UAVs and geodetic techniques to monitor ground deformation within the Choirokoitia UNESCO World Heritage Site in Cyprus. The Neolithic settlement of Choirokoitia, occupied from the 7th to the 4th millennium B.C., is one of the most important prehistoric sites in the eastern Mediterranean. The study is conducted under the PROTHEGO (PROTection of European Cultural HEritage from GeO-hazards) project, which is a collaborative research project funded in the framework of the Joint Programming Initiative on Cultural Heritage and Global Change (JPICH)-Heritage Plus in 2015-2018 (www.prothego.eu) and through the Cyprus Research Promotion Foundation. PROTHEGO aims to make an innovative contribution towards the analysis of geo-hazards in areas of cultural heritage, and uses novel space technology based on radar interferometry to retrieve information on ground stability and motion in the 400+ UNESCO's World Heritage List monuments and sites of Europe. The field measurements collected at the Choirokoitia site will be later compared with SAR data to verify micro-movements in the area to monitor potential geo-hazards. The site is located on a steep hill, which makes it vulnerable to rock falls and landslides.
Keywords: Cultural heritage; JPI; UAV; Remote sensing; Prothego; Natural hazards; Geodetic techniques